CaMKII activation in early diabetic hearts induces altered sarcoplasmic reticulum‑mitochondria signaling - Federico, Marilén (2021)
Prediabetic myocardium, induced by fructose-rich diet (FRD), is prone to increased sarcoplasmic reticulum (SR)-Ca2+ leak and arrhythmias due to increased activity of the Ca2+/ calmodulin protein kinase II (CaMKII). However, little is known about the role of SR-mitochondria microdomains, mitochondrial structure, and mitochondrial metabolisms. To address this knowledge gap we measured SR-mitochondrial proximity, intracellular Ca2+, and mitochondrial metabolism in wild type (WT) and AC3-I transgenic mice, with myocardial-targeted CaMKII inhibition, fed with control diet (CD) or with FRD. Confocal images showed significantly increased spontaneous Ca2+ release events in FRD vs. CD WT cardiomyocytes. [ 3H]-Ryanodine binding assay revealed higher [ 3H]Ry binding in FRD than CD WT hearts. O2 consumption at State 4 and hydrogen peroxide ( H2O2) production rate were increased, while respiratory control rate (RCR) and Ca2+ retention capacity (CRC) were decreased in FRD vs. CD WT isolated mitochondria. Transmission Electron Microscopy (TEM) images showed increased proximity at the SR-mitochondria microdomains, associated with increased tethering proteins, Mfn2, Grp75, and VDAC in FRD vs. CD WT. Mitochondria diameter was decrease and roundness and density were increased in FRD vs. CD WT specimens. The fission protein, Drp1 was significantly increased while the fusion protein, Opa1 was unchanged in FRD vs. CD WT hearts. These differences were prevented in AC3-I mice. We conclude that SR-mitochondria microdomains are subject to CaMKII-dependent remodeling, involving SR-Ca2+ leak and mitochondria fission, in prediabetic mice induced by FRD. We speculate that CaMKII hyperactivity induces SR-Ca2+ leak by RyR2 activation which in turn increases mitochondria Ca2+ content due to the enhanced SR-mitochondria tethering, decreasing CRC.